ASSOCIATION OF SINGLE NUCLEOTIDE POLYMORPHISMS IN NOD1 AND NLRP9 GENES WITH FECAL EGG COUNT TRAIT OF CHINESE AND BANGLADESHI GOAT BREEDS BEING NATURALLY INFECTED BY HAEMONCHUS CONTORTUS - A. I. Omar; L. Yin; S. Inayat; M. B. B. Alam; W. Zhenyang; T. Worku; T. N. T. Thi; M. O. Faruque; K. Periasamy; M. Samsuddin; S. Zhao; X. Du; et al. (Journal of Animal and Plant Sciences, 2019)
The study was conducted to identify relationships between single nucleotide polymorphisms (SNPs) in the NOD1 and NLRP9 genes and resistance to H. contortus infestation in goats in China and Bangladesh. A total of 507 unrelated goats from 6 different populations were sampled. Fecal egg count (FEC) was determined and genomic DNA was extracted from those goats. Touchdown PCR assays were used to genotype each of the target SNP. An association study was carried out using a generalized linear model and R software after transforming the FEC as log10 (FEC + 25). All breeds of goat in Bangladesh had lower mean FEC than any of the Chinese breeds. Two single nucleotide polymorphisms (SNPs) viz. NOD1_146_A>G (p<0.001) and NLRP9_43_A>G (p<0.003) were significantly associated with FEC trait after H. contortus infection. Goats with the GG genotype for NOD1_146_A>G (904.43 ± 140.65epg) and the AA genotype for NLRP9_43_A>G (1129.57 ± 196.5 epg) had higher FEC than goats with the AA genotype (396.68 ± 67.22 epg) or the GG genotype (399.12 ± 106.4 epg) at the respective loci. NOD1 and NLRP9 genes were significantly associated with FEC and might be related to resistance to H. contortus infection in goats.
Keywords: Goat; Haemonchus contortus; fecal egg count; parasitic resistance; SNP